2013
DOI: 10.1044/1092-4388(2013/12-0188)
|View full text |Cite
|
Sign up to set email alerts
|

Grammatical Outcomes of 3- and 6-Year-Old Children Who Are Hard of Hearing

Abstract: Purpose Spoken language skills of 3- and 6-year-old children who are hard of hearing (HH) were compared to those of children with normal hearing (NH). Method Language skills were measured via MLU in words and percent correct use of finite verb morphology in obligatory contexts based on spontaneous conversational samples gathered from 185 children (145 HH; 40 NH). Aided speech intelligibility index (aided SII), better ear pure tone average (BE-PTA), maternal education, and age of amplification were used to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 59 publications
(86 reference statements)
9
61
0
1
Order By: Relevance
“…As described at the beginning of this article, the current findings support the notion that grammar is particularly vulnerable to the effects of inconsistent auditory access, especially in the case of morphological markers that have short duration and reduced perceptual salience (e.g., third-person singular; "he walks"; Leonard, 1989). These results, in combination with others (Koehlinger et al, 2013;McGuckian & Henry, 2007), also highlight how early, consistent access to auditory information can serve as a protective mechanism for acquiring English morphological markers (as in the case of the full-time users). Note.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…As described at the beginning of this article, the current findings support the notion that grammar is particularly vulnerable to the effects of inconsistent auditory access, especially in the case of morphological markers that have short duration and reduced perceptual salience (e.g., third-person singular; "he walks"; Leonard, 1989). These results, in combination with others (Koehlinger et al, 2013;McGuckian & Henry, 2007), also highlight how early, consistent access to auditory information can serve as a protective mechanism for acquiring English morphological markers (as in the case of the full-time users). Note.…”
Section: Discussionsupporting
confidence: 78%
“…For example, McGuckian and Henry (2007) showed that 7-year-old children with moderate HL demonstrated poor performance on measures of English morphology. Koehlinger et al (2013) examined language samples of 3-and 6-year-old children in the OCHL cohort and found that children with more auditory access (i.e., better audibility and younger ages at HA fitting) produced more obligatory verb morphemes compared with children with less auditory access. As described at the beginning of this article, the current findings support the notion that grammar is particularly vulnerable to the effects of inconsistent auditory access, especially in the case of morphological markers that have short duration and reduced perceptual salience (e.g., third-person singular; "he walks"; Leonard, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on children with CIs and HAs frequently reports delays in the acquisition of syntax and morphology, indicating that this is a vulnerable language area for both groups (Brown 1984;Elfenbein and Hardin-Jones 1994;Norbury et al 2001;Young & Killen 2002;Wake et al 2004;Borg et al 2007;Hansson et al 2007;McGuckian & Henry 2007;Geers et al 2009;Hawker et al 2008;Moeller et al 2010;Caselli et al 2012;Koehlinger et al 2013). These studies show that school-age children with hearing loss produce more errors in the production of different types of morphemes, including determiners (e.g., a, the), pronouns (e.g., me, him), plural nouns (e.g., apples), and past tense (e.g., he walked).…”
Section: Morphological Development In Children With Hearing Lossmentioning
confidence: 97%
“…Further research has shown that daily HA use influences language outcomes in early school-age children with mild HL, particularly for morphosyntactic acquisition (Walker, Holte, et al, 2015). Access to high-frequency information is especially important because many English morphological markers consist of high-frequency, low-intensity phonemes (Koehlinger, Van Horne, & Moeller, 2013;Koehlinger, Van Horne, Oleson, McCreery, & Moeller, 2015;Stelmachowicz, Pittman, Hoover, & Lewis, 2002;Stelmachowicz, Pittman, Hoover, Lewis, & Moeller, 2004). Furthermore, children with mild HL will frequently encounter situations in which background noise and distance could have negative effects on the ability to learn language.…”
Section: Parental Attitudes Toward Intervention and Amplificationmentioning
confidence: 99%